Unpredictable Response of Pseudomonas aeruginosa to Synergistic Antibiotic Combinations In Vitro - Heineman, Herbert S. (1978)
The combined activity of ticarcillin and each of three aminoglycosides, gentamicin, tobramycin, and amikacin, was studied with 45 clinical isolates of Pseudomonas aeruginosa. All strains individually were susceptible to each of these agents. Comparison of the results revealed highly variable interaction, both from strain to strain and from one aminoglycoside to another against the same strain. Against 11 strains, none of three antibiotic pairs tested was synergistic by conventional criteria; against the remaining 34, three, any two, or any one pair among those tested was synergistic. The minimal inhibitory concentrations of individual drugs gave no indication of the degree of synergism to be expected. We conclude that generalizations about the behavior of this organism vis-à-vis penicillin-aminoglycoside combinations in vitro are subject to many exceptions. Furthermore, no test using a particular antibiotic combination is reliable as a screen for other combinations. If this experience is duplicated in vivo, combination testing may be as important for the choice of combination therapy as individual susceptibility testing is for the choice of individual antibiotics.